THE EFFECTS OF WORD OF MOUTH AND SALES PROMOTION ON PURCHASING DECISION FOR DREAMLAND DECORATION - Anggraini, Cynthia Anggraini; Melinda, Tina (Jurnal Entrepreneur dan Entrepreneurship, 2018)
Business development in Indonesia grows rapidly, especially in trade and service field. Due to the economy growth, service industry must be more creative and innovative in creating products, one of them is decoration service. Dreamland Decoration is the company in service field that was established in 2014. Dreamland Decoration accepts orders such as table setting, sweet corner, birthday surprise with unique theme and creative design. This research is done to found out the influence of word of mouth and sales promotion on consumer purchasing decision in using service of Dreamland Decoration. This research uses quantitative method and multiple regression analysis model by involving Dreamland Decoration customers as 80 respondents then is processed by using SPSS 22. The result of this research that has been done states that word of mouth and sales promotion have positive influence on consumer decision in using Dreamland Decoration service.